Financing Model for Construction and Demolition Waste in Indonesia - Susilowati, Fajar; Prakoso, Jalu Aji; Adipradana, Arrizka Yanuar (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Construction waste poses a significant environmental and economic challenge in Indonesia’s rapidly expanding construction sector. This research develops a financing model for managing construction waste throughout the project life cycle, emphasizing the integration of cost components and waste management strategies. Data were collected through surveys, structured interviews, and observations from 80 construction projects across Indonesia. The analysis revealed that while reinforcement, bricks, and split stone have high recycling potential, actual reuse remains limited due to poor planning and insufficient infrastructure. Seven financing components were identified: material loss, production/management, sorting, collection, transportation, recycling, and dumping. Notably, material loss accounts for the largest cost share—up to 10% of project value—while recycling and dumping costs are underfunded at 0.01%–0.5%. A cost-based model was developed to simulate waste-related expenses, ranging from 0.39% to 20.5% of overall project costs. The research also highlights the design stage as a critical leverage point for maximizing waste reduction. By aligning financial planning with life cycle stages, this research provides practical guidance for stakeholders and supports Indonesia’s transition to a circular construction economy through better budgeting, policy development, and waste strategy implementation.